Empowering and Protecting Local Products: The Implementation of SMEs Product Protection and Legality in Lerep Village Indonesia - Maulana, Muhammad Reza; Ramadhani, Fauziah; Niravita, Aprila; Lestari, Sri (Universitas Negeri Semarang, 2021)
SMEs are a source of livelihood for small and medium communities in areas in Indonesia. Currently, the government is actively assisting SMEs players in building their businesses in order to improve the family economy and the economy of the people in the region. The size of the contribution of SMEs in supporting the economy of a country so that the existence of SMEs is highly expected by any country because of its vital role in the development and progress of the economy to achieve people's welfare. The establishment of a business in the SMEs sector is able to absorb the number of workforces who are ready to work but have not yet got a job so that it can reduce the number of unemployed. In establishing a business, SMEs actors should have a legality license or business license to run their business. The importance of legality for SMEs activists is that in running their business entrepreneurs do not need to be confused when their merchandise or business is tested to find out the feasibility and legality of the business they are running. Implementation in the ease of granting permits for SMEs is still not possible in all regions because there are still regional heads who have not issued regulations to delegate the authority to issue SMEs permits to sub-districts. Business licenses or SMEs that have received legality of their products to get it easier in running their business. Business licensing provisions that need to be owned by entrepreneurs in the form of Company Business License are based on the Regulation of the Minister of Trade No. 46/2009 concerning Amendments to Permendag No.36/2007 concerning Issuance of Trading Business Permits.